Implementation of the Employee Payroll and Wage Accounting System at the Investment and One-Stop Integrated Service Office of North Sumatra Province - Mela Andriani Hasibuan; Minasari Nasution; Abdul Gani (Jurnal Multidisiplin Sahombu, 2025)
This research aims to analyze the implementation of the payroll accounting system and employee wages at the North Sumatra One Stop Integrated Services and Investment Service. An effective accounting system is very important in supporting the smooth process of employee payroll and wages, as well as ensuring accuracy and efficiency in financial recording. This research uses a qualitative descriptive method. And data is collected through observation, interviews and documentation related to payroll and wage processes. The research results show that the accounting system currently implemented has helped increase efficiency and accuracy in the payroll and wage process. It can be concluded that the implementation of the payroll accounting system uses a government regulatory system and is in accordance with applicable government regulations. The author concludes that the North Sumatra One Stop Investment and Integrated Services Service is adequate.